Pattern of Practices of General Physicians in Overt Diabetic Nephropathy- A Pilot Study in A Developing Country (BIRDEM Medical Journal, 2017)
Introduction: Diabetes is the most common cause of chronic kidney disease (CKD) and end-stage renal disease (ESRD) in most parts of the world. Around 20 to 30% of type 1 and type 2 diabetic patients have diabetic nephropathy. General physicians can play an important role in the detection of diabetic nephropathy (DN) and its early primary management and thus prevent its long term dreaded complications. This study was designed to assess the levels of physicians practice, working in diabetic care facilities in terms of early detection and management of DN.Method: A cross-sectional study was conducted among Physicians working in various affiliated associations of Diabetic Association of Bangladesh (DAB), using a pre-validated self-administered questionnaire. It was conducted in the month of April 2016. Data were collected based on the printed series of questionaries regarding “the actions when overt proteinuria was first detected in Urine R/M/E or conventional dipstick test”.Results: In total, 51 general physicians were included. The average age was 34.39 ± 8.54 years ranging from 25 to 64 years. Thirty (58.9 %) of them are in younger age group (25-34 age range) others in senior group (35- 64). A male predominance was observed with 1.5 sex ratio. Twenty-two (43.1%) of them had undergone a Certified Course on Diabetes (CCD). Regarding intervention following first ever detection of overt proteinuria only 29.41% wanted to investigate further and 58.8% wants to repeat the test. To see the extent of renal damage 58.8 and 74.5% of the physicians wanted to do 24-hours urinary total protein (24-h UTP) and serum creatinine respectively. Twenty-seven (52.9%) physicians thought it is right to use angiotensin converting enzyme (ACE) inhibitors / angiotensin receptor blockers (ARBs) for proteinuria. Thirty-three (64.7%) of them wanted to refer to a nephrologist for proteinuria. To see the presence of other microvascular complications, 52.9 % of doctors wanted to examine for the presence of neuropathy and 62.7% wanted to exclude retinopathy by examining the fundus or referring the patient to an ophthalmologist.Conclusion: Overall, the collective response of the doctors having done Certificate Course on Diabetes were much better than others. Junior doctors also fare better than seniors.Birdem Med J 2018; 8(1): 63-67